Using emoji in response to customer reservation requests and service reviews - Prada, M.; Saraiva, M.; Cruz, S.; Xavier, S.; Rodrigues, D. L. (Human Behavior and Emerging Technologies, 2022)
The use of paralinguistic cues—including emoji—in computer-mediated communication has become prevalent in recent years. Brands and service providers have also been using these cues in their communication strategies. And yet, research examining how such emoji use influences customers’ perception and behavior is still scarce. In two experiments (combined ), we tested if using emoji to reply to a customer request (restaurant reservation, Study 1) or online review (hotel experience, Study 2) influenced perceptions of the brands. The emoji used by the brand was always congruent with the valence of the situation. Results from both studies revealed that the presence (vs. absence) of emoji influenced consumers’ perception of the brand/service at several levels. Specifically, the restaurant/hotel was perceived to have a more informal communication style, have a warmer service, and be more modern. In Study 1, we also observed that emoji use had a positive impact on competence perception and reservation intentions. Importantly, these effects of emoji use were not moderated by the valence of the situation. Taken together, our results showed that emoji can influence different perceptions about brands and services and determine how customers relate to brands.